Prevalence and predictors of asthma, tuberculosis and chronic bronchitis among male tannery workers: A study of Kanpur City, India - Gyan Chandra Kashyap; Santosh Kumar Sharma; Shri Kant Singh (Elsevier, 2021)
Background: In India, it was reported previously about varying prevalence of asthma and chronic bronchitis among leather tannery workers with moderate to high exposures at the workplace to be significantly associated with asthma. This study intended to estimate the prevalence of asthma, tuberculosis, and chronic bronchitis among leather tannery workers and to identify the risk factors associated with it. Data and Methods: The data used in this study were collected through a cross-sectional household survey of 284 male tannery workers in the Jajmau area of Kanpur city in the state of Uttar Pradesh, during January-June 2015. A binary logistic regression analysis was performed to identify the factors associated with respiratory symptoms. Results: The prevalence Asthma and Chronic Bronchitis among Tannery workers was 12.3% and 11.6% which is higher as compared to non-tannery workers. The findings revealed that the prevalence of symptoms suggestive of asthma, tuberculosis, and chronic bronchitis among the tannery workers was higher compared to non-tannery workers. The study revealed that long time tannery working harms health, as tannery workers are more likely to be suffering from asthma and chronic bronchitis who worked above 11 years in the tannery (p < 0.62). Conclusion: The study concludes that age, education, media exposure, working hours in the tannery, type of work engagement within tannery occupation, and exposure to chemicals are the major risk factors for asthma, tuberculosis, and chronic bronchitis among the male tannery workers. Specific health insurance facilities should be provided, such as the Employee's State Insurance Scheme (ESIS), from the day a person begins work in a tannery.